Jahrbuch für Kulturpolitik 2015/16. Transformatorische Kulturpolitik - Knoblich J., Tobias; Föhl S., Patrick; Sievers, Norbert (2016)
With the realisation of German unity, cultural policies have also changed - conceptually as well as instrumentally. It would be too short-sighted, however, if one were to frame this transformation as the direct result of German unity. It is also necessary to take into account that it occures in the context of a not only European but also global social shift. The "2015 Yearbook for Cultural Politics" contains the contributions from the eighth Federal Congress for Cultural Politics, entitled "Kultur.Macht.Einheit?" ("Culture.Power.Unity?"), which featured presentations be figures such as Monika Grütters, Wolfgang Thierse, Norbert Lammert, and Tim Renner. Additional articles extrapolate on this extensive field and broaden the range of perspectives on the phenomenon of transformation. Mit der Verwirklichung der deutschen Einheit hat sich auch die Kulturpolitik verändert – sowohl konzeptionell wie instrumentell. Dieser Transformationsprozess wäre jedoch zu kurz gedacht, wenn man sie nur auf die unmittelbaren Folgen der deutschen Einheit beziehen würde. Man muss auch in Rechnung stellen, dass er sich im Rahmen eines nicht nur europäischen, sondern globalen gesellschaftlichen Wandels ereignet. Das »Jahrbuch für Kulturpolitik 2015/16« enthält die Beiträge des 8. Kulturpolitischen Bundeskongresses 2015 »Kultur.Macht.Einheit?«, auf welchem u.a. Monika Grütters, Wolfgang Thierse, Norbert Lammert und Michael Schindhelm referierten. Zusätzliche Fachartikel erschließen diesen umfangreichen Kontext und verbreitern die Perspektive auf das Phänomen kulturpolitischer Transformation.